El cuidado del medio ambiente - Ayala Chusin, Nancy Rosario (2017)
The care of the environment is a social responsibility that requires a wide knowledge on the part of all the people to develop an awareness and to be an actor of the environmental preservation. The excessive use of paper for work, evaluations, research and academic tasks in educational institutions requires the knowledge and application of recycling strategies to generate a sense of responsibility with the ecosystem, which allows to reduce the pollution produced by the excessive use of unitary sheets and notebooks for each of the subjects and activities carried out in the teaching-learning processes in the educational field. The present work has as purpose to describe characteristics of environmental care and recycling in children of the third year of Basic Education of the Unidad Educativa "Vicente león" of the canton Latacunga, period 2017. The methodology is based on research with a quantitative approach because it generalizes the results found in the applied population, whose studies can be replicated in other institutions. According to the methodological design, the documentary and field research and the deductive-inductive method were carried out. The need for environmental care is a social requirement. For this reason, the formation of an environmental conscience and responsibility must be promoted, which guarantees an adequate waste management, such as the role that through artistic recycling can be converted into functional products and Aesthetics. The present work aims to directly benefit the children of the institution by encouraging in the educational community the discussion on environmental care, recycling and sustainable development. It seeks to generate an educational process consistent with current social needs to encourage the use of new strategies that improve the quality of education from environmental education. This project aims to encourage children, teachers and parents to seek strategies for sustainable development that contribute to improving environmental care with awareness and responsibility.